Determination of Glucose in Human Serum Using Background Subtraction of Cyclic Voltammetry of a Low Oxidation Peak at NiO Based Electrode. Issue 2 (4th February 2022) - Dung, Nguyen Quoc; Toan, Tran Quoc; Sedthiphonh, Serth; Truong, Mai Xuan; Thi Hue, Tran; Thi Ha Thanh, Pham; Lam, Tran Dai; Dung, Dang Duc; Huy, Nguyen Nhat; Thanh, Dang Van
Abstract : In this study, the background subtraction of cyclic voltammetry of a low oxidation peak at NiO based electrode is employed for the determination of glucose in human serum in 0.1 M NaOH medium with 2 linear ranges of 10 to 100 μ M and 100 to 2000 μ M with a detection limit of 2 μ M and the sensitivities of 2942.2 and 754.2 μ Acm −2 mM −1, respectively. As a result, determining the glucose concentration in the real sample shows that this type of NiO-based sensor can be used in practice and approach to accurately determining the glucose concentration in human serum.